2011
DOI: 10.4062/biomolther.2011.19.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Future Cancer Therapy with Molecularly Targeted Therapeutics: Challenges and Strategies

Abstract: In a pharmaceutical industry in which nine out of ten attempts to bring a product to market fail, oncology is among the most challenging therapeutic area (Kola and Landis, 2004;Kamb et al., 2007). In the recent article published in the Nature Rev. Drug Discov. (Arrowsmith, 2011), 83 Phase III and submission failures during 2007 to 2010 were divided according to therapeutic area and reason for failure. Largest numbers of failures was in the area of cancer (28%) followed by neurodegeneration (18%). The 66% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 170 publications
(210 reference statements)
0
3
0
Order By: Relevance
“…3 The key step in the development of an effective cancer treatment is based on the identification of the biological characteristics and/or pathways of individual tumors. 4 Regarding melanoma cancer, several mutations have been used to develop specific treatments (CDKN2A, CDK9, NSRAS, and BRAF). 5 Other targets have also been identified and investigated, such as sigma-1 and melanocortin-1 receptors and melanin pigments.…”
mentioning
confidence: 99%
“…3 The key step in the development of an effective cancer treatment is based on the identification of the biological characteristics and/or pathways of individual tumors. 4 Regarding melanoma cancer, several mutations have been used to develop specific treatments (CDKN2A, CDK9, NSRAS, and BRAF). 5 Other targets have also been identified and investigated, such as sigma-1 and melanocortin-1 receptors and melanin pigments.…”
mentioning
confidence: 99%
“…Further experiments with glutathione in the reaction media showed that the Dox-loaded nanogels are essentially nontoxic before addition of the reducing agent (see Fig. (2), 48 h mark), but after the reducing agent is added, the drug is released, and the cell growth is significantly inhibited due to the contact with the drug (96 h in Fig. (2)).…”
Section: Nanosystems Based In Stimulus-responsive Hydrogelsmentioning
confidence: 99%
“…Despite the search of novel anticancer drugs is a very active, burgeoning research area which has provided many promising results in the last decade [1,2], the biopharmaceutical and pharmacokinetical aspects of current and future anticancer drug therapies are particularly critical aspects to achieve favorable clinical outcome in the field of oncology. In other words, the development of novel chemotherapies should be complemented with innovative drug delivery devices.…”
Section: Introductionmentioning
confidence: 99%